Anteseden Urge to Buy Impulsively: Studi Beauty Vlog pada Sosial Media Youtube - Vivi Rodliyatuz Zulfa (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2020)
This study aims to determine the effect of parasocial interaction, perceived enjoyment, perceived usefulness, and negative affect of social media users on the urge to buy impulsively. Data was taken by distributing questionnaires online involving 189 female respondents who watched the beauty blog video on Youtube. The location of this research in Indonesia. Hypothesis testing using Partial Least Squares (PLS). The results of the study show that parasocial interaction, perceived enjoyment, perceived usefulness affect the urge to buy impulsively. In contrast, negative affect harms the urge to buy impulsively. The results of this study have implications for cosmetics marketers who use YouTube as one of their marketing media in improving marketing strategies that are more effective in attracting users through impulsive buying.